1986
DOI: 10.7326/0003-4819-104-3-298
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Hypovolemia

Abstract: Eleven patients with orthostatic intolerance had, for no detectable reason, a marked reduction in blood volume (73 +/- 2.29% [SE] of normal). Head-up tilt caused a pronounced increase in heart rate (+ 39 +/- 6 beats/min); one patient had a vasovagal episode after the initial tachycardia. Extensive diagnostic study excluded pheochromocytoma, hypoaldosteronism, or any obvious cause for hypovolemia (total plasma catecholamines, 372 +/- 53 ng/L; plasma aldosterone level, 14.5 +/- 2.56 ng/100 mL; plasma cortisol le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
85
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(90 citation statements)
references
References 0 publications
2
85
0
3
Order By: Relevance
“…Symptoms are associated with inadequate systemic venous return to the right heart or thoracic hypovolemia, although precise mechanisms remain to be clarified. 4,5,25 In addition, reduced cerebral perfusion induced by excessive lowerbody venous pooling with delayed orthostatic hypotension has been suggested to be involved in the orthostatic component of fatigue in CFS patients. 26 Recently, by using a cardiac magnetic resonance imaging technique, Fu et al 13 assessed precisely the heart size and mass in patients with POTS and found that cardiac size and mass and blood volume were much smaller in the patients than in healthy sedentary controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Symptoms are associated with inadequate systemic venous return to the right heart or thoracic hypovolemia, although precise mechanisms remain to be clarified. 4,5,25 In addition, reduced cerebral perfusion induced by excessive lowerbody venous pooling with delayed orthostatic hypotension has been suggested to be involved in the orthostatic component of fatigue in CFS patients. 26 Recently, by using a cardiac magnetic resonance imaging technique, Fu et al 13 assessed precisely the heart size and mass in patients with POTS and found that cardiac size and mass and blood volume were much smaller in the patients than in healthy sedentary controls.…”
Section: Discussionmentioning
confidence: 99%
“…31 Volume repletion by increasing sodium intake or by treatment with fludrocortisones may theoretically improve OI and also symptoms of CFS by replenishing intravascular volume. 4,7,9,22,25 Military antishock trousers and elastic stockings may also be effective via potentiation of venous return, resulting in increased cardiac output. 26 Although CFS patients are limited by the discomfort of an increased perception of exertion, there are some data to support the notion that an appropriately designed exercise program is beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…1 POTS produces redistributive hypovolemia related to neurovascular deficiencies. 2,3 Thus, Jacob et al 4 demonstrated a low-renin form of hypovolemia in some patients, whereas a decrease in norepinephrine spillover consistent with lower limb adrenergic denervation has been shown 5 and predicts blunted arterial vasoconstriction consistent with inappropriate vasodilation as demonstrated by Stewart. 6 Enhanced blood flow in POTS occurs in the supine and upright positions, producing lower limb enlargement, 7 often referred to as "dependent [venous] pooling," assuming that excess blood is sequestered or "pooled' within the leg veins.…”
mentioning
confidence: 99%
“…Many patients with POTS are so debilitated by their orthostatic symptoms, they are unable to work. 2 A number of different pathophysiologies underlie symptoms in subgroups of patients, [3][4][5][6][7][8][9][10][11][12][13][14] but the basis of POTS remains obscure in most afflicted individuals. Genes encoding the NE transporter (SLC6A2), 13 the ␤-1 15 and ␤-2 (G. Jacob, unpublished data, 2005) adrenergic receptors, and endothelin-1 (R. Winker, unpublished data, 2005) are associated with the development of POTS.…”
mentioning
confidence: 99%